An investigation of the effects of dual-task balance exercises on balance, functional status and dual-task performance in children with Down syndrome - Buyukcelik, Neslinur Merve; Yigit, Sedat; Begümhan Turhan (An investigation of the effects of dual-task balance exercises on balance, functional status and dual-task performance in children with Down syndrome)
PurposeTo investigate the effects of dual task (DT) balance exercises on functional status, balance, and DT performance in children with Down Syndrome (DS).MethodsParticipants were divided into two groups: intervention group (IG; n = 13) and control group (CG;n = 14). WeeFIM was used to measure the functional independence level and balance was evaluated using the Pediatric Balance Scale. DT performance was assessed using Timed Up and Go, Single Leg Stance, Tandem-Stance and 30 s Sit to Stand tests without concomitant task, with motor task or cognitive task. The IG received 16 sessions of DT training twice a week for 8 weeks.ResultsFunctional level, balance, and DT performance improved significantly in the IG, whereas only balance improved in the CG. Significantly better results were achieved in the IG, as demonstrated by greater pre/post-treatment changes.ConclusionDT balance exercises improved functional level, balance and DT performance of children with DS.
Keywords: motor skills; dual task; Down syndrome; cognition; balance